The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1113/jphysiol.1985.sp015718
|View full text |Cite
|
Sign up to set email alerts
|

Different types of slowly conducting afferent units in cat skeletal muscle and tendon.

Abstract: SUMMARY1. In chloralose-anaesthetized cats, the impulse activity of single afferent units conducting at less than 30 m sol and having receptive fields in the triceps surae muscle or the calcaneal tendon, was recorded from thin filaments of the dorsal roots L7 and SI. The receptive fields of the units were tested with a variety of graded natural stimuli (local pressure, stretch, contractions, temperature changes). In addition, the algesic agent bradykinin was injected into the receptive fields, but the sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
122
3
5

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(144 citation statements)
references
References 21 publications
14
122
3
5
Order By: Relevance
“…These values were about the half those of the cutaneous thin fiber receptors measured by our group with the same instruments in vivo and in vitro (Suzuki et al 2002;Takahashi et al 2003). The existence of thin-fiber receptors with low and high mechanical threshold in the muscle has been reported (Mense and Meyer 1985). However, the distribution of the mechanical thresholds was continuous in the present study and no natural segregation into subgroups was observed.…”
Section: Thin-fiber Receptor Recording In Muscle-nerve Preparation Incontrasting
confidence: 54%
“…These values were about the half those of the cutaneous thin fiber receptors measured by our group with the same instruments in vivo and in vitro (Suzuki et al 2002;Takahashi et al 2003). The existence of thin-fiber receptors with low and high mechanical threshold in the muscle has been reported (Mense and Meyer 1985). However, the distribution of the mechanical thresholds was continuous in the present study and no natural segregation into subgroups was observed.…”
Section: Thin-fiber Receptor Recording In Muscle-nerve Preparation Incontrasting
confidence: 54%
“…Small-diameter afferents from muscle, tendons (Mense and Meyer, 1985) and joints (Schiable and Schmidt, 1983) have been studied in the cat and consist of a mixture of low-and high-threshold units, with the majority of C-fibers falling into the latter category. C-fibers terminate in the superficial dorsal horn (Light and Perl, 1979) where many intemeurons are excited directly or indirectly by the arrival ofa volley in C-afferents (Fitzgerald and Wall, 1980;Woolf and Fitzgerald, 1983).…”
mentioning
confidence: 99%
“…A major proportion of small diameter group III and IV muscle afferents are sensitive to noxious mechanical and chemical stimuli (Mense and Meyer 1985;Mense and Stahnke 1983). According to the pain adaptation model (Lund et al 1991), the activity of thin nociceptive muscle afferents facilitates inhibitory pathways when the muscle acts as an agonist and facilitates excitatory pathways during antagonist activity.…”
Section: Introductionmentioning
confidence: 99%